2020
DOI: 10.1101/2020.04.20.051664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The cationic amino acid exporter Slc7a7 is vital for and induced in tissue macrophages with sustained efferocytic activity

Abstract: Most tissues harbor a substantial population of resident macrophages. It is not quite known yet how their quite diverse phenotypes are shaped by the functions that they assume in each tissue. In this study, we elucidate a functional link between the Slc7a7 cationic amino acid transporter and tissue macrophages. We had identified a mutant zebrafish devoid of microglia due to a mutation in the slc7a7 gene. We found that in Slc7a7 deficient larvae, macrophages do enter the retina and brain to become microglia, bu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Chronic renal injury could also be generated by inflammatory processes secondary to dysregulated immune activation caused by excess NO production (78). Efferocytosis is the process by which macrophages and other phagocytic cells remove apoptotic cells; recently Demy et al showed that y+LAT1 is expressed shortly after efferocytosis in microglia and other tissue resident macrophages allowing them to preserve their own viability during phagocytosis, defects in macrophage phagocytic function could contribute to both neurologic and immunologic finding in patients with LPI (79).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic renal injury could also be generated by inflammatory processes secondary to dysregulated immune activation caused by excess NO production (78). Efferocytosis is the process by which macrophages and other phagocytic cells remove apoptotic cells; recently Demy et al showed that y+LAT1 is expressed shortly after efferocytosis in microglia and other tissue resident macrophages allowing them to preserve their own viability during phagocytosis, defects in macrophage phagocytic function could contribute to both neurologic and immunologic finding in patients with LPI (79).…”
Section: Discussionmentioning
confidence: 99%